Control of cytokine production by human Fc gamma receptors: implications for pathogen defense and autoimmunity - Vogelpoel, Lisa T.; Baeten, Dominique L.; de Jong, Esther C.; Den Dunnen, Jeroen (Frontiers in Immunology, 2015)
Control of cytokine production by immune cells is pivotal for counteracting infections via orchestration of local and systemic inflammation. Although their contribution has long been underexposed, it has recently become clear that human Fc gamma receptors (FcγRs), which are receptors for the Fc region of IgG antibodies, play a critical role in this process by controlling tissue and pathogen-specific cytokine production. Whereas individual stimulation of FcγRs does not evoke cytokine production, FcγRs cell-type specifically interact with various other receptors for selective amplification or inhibition of particular cytokines, thereby tailoring cytokine responses to the immunological context. The physiological function of FcγR-mediated control of cytokine production is to counteract infections with various classes of pathogens. Upon IgG opsonization, pathogens are simultaneously recognized by FcγRs as well as by various pathogen-sensing receptors, leading to the induction of pathogen-class specific immune responses. However, when erroneously activated the same mechanism also contributes to the development of autoimmune diseases such as rheumatoid arthritis and systemic lupus erythematosus. In this review, we discuss control of cytokine production as a novel function of FcγRs in human innate immune cells in the context of homeostasis, infection, and autoimmunity and address the possibilities for future therapeutic exploitation.